Anti-DPPX-Encephalitis in A Patient with Cerebral Vasculitis and Connective Tissue Disease - Krause Eva; Rizos Timolaos; Sohendra Mike; Blank Norbert; Meinck Hans-Michael; Schönenberger Silvia; Nagel Simon (Journal of Neurological Research And Therapy, 2018)
Since the first description in 2013, 39 cases of anti-DPPX-encephalitis have been described. Main features of this autoimmune encephalitis characterized by antibodies against the potassium-channel-associated regulatory protein DPPX are gastrointestinal symptoms, cognitive dysfunction and signs of CNS hyperexcitability. While the majority of patients responds to immunotherapy relapses are frequent and often successfully treated with rituximab. Here we report another case of anti-DPPX-encephalitis presenting with the above mentioned triad. However, this is the first case of anti-DPPX-encephalitis in the context of a connective tissue disease combined with cerebral arteriopathy along with brain parenchymal lesions that we interpreted as a secondary, CTD-associated cerebral vasculitis. While the latter resolved under immunosuppressive treatment, comprising glucocorticosteroids, cyclophosphamide, rituximab and plasmapheresis, deterioration of the CTD and multiple infectious complications finally led to the patient's death. As histological evidence for cerebral vasculitis is lacking, other differential diagnoses for the observed cerebral arteriopathy, especially reversible cerebral vasoconstriction syndrome, have to be considered.
Keywords: DPPX